2014
DOI: 10.1161/strokeaha.113.003454
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Bifurcation Geometry Is an Independent Predictor of Early Wall Thickening at the Carotid Bulb

Abstract: Background and Purpose Lumen geometry has long been suspected as a risk factor for atherosclerosis by virtue of its influence on blood flow disturbances. Confirmation of this geometric risk hypothesis has, however, proved challenging owing to possible effects of wall thickening on geometry, and unproven links between candidate geometric variables and disturbed flow. The purpose of this study was to overcome these challenges. Methods The study relied on imaging and risk factor data from progressively refined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
71
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(82 citation statements)
references
References 26 publications
5
71
1
3
Order By: Relevance
“…28 Ϯ 11°, P ϭ 0.52) and 4 (46 Ϯ 17°vs. 51 Ϯ 16°, P ϭ 0.14), which was consistent with the results of Bijari et al (3). In contrast, Phan et al (23) found a significant increase of the ICA angle in adults with mild and severe stenoses.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…28 Ϯ 11°, P ϭ 0.52) and 4 (46 Ϯ 17°vs. 51 Ϯ 16°, P ϭ 0.14), which was consistent with the results of Bijari et al (3). In contrast, Phan et al (23) found a significant increase of the ICA angle in adults with mild and severe stenoses.…”
Section: Discussionsupporting
confidence: 89%
“…Although a complete comparison showed significant difference of carotid artery bifurcations between control subjects and patients with carotid artery disease, the sample size (30 control subjects and 30 patients with carotid artery disease) in the retrospective study was relatively small compared with previous studies (3,23). This requires further analysis with larger sample size in a prospective study.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations